Community empowerment through the MyKasih entrepreneurship program towards urban poverty alleviation in Kuala Lumpur, Malaysia - Dass, Mahaganapathy; Gill, Sarjit S.; Kunasekaran, Puvaneswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper presents the level of empowerment gained by the urban poor minorities of MyKasih program participants towards urban poverty alleviation in Kuala Lumpur, Malaysia. MyKasih is one of the few Non-governmental Organization focused to combat urban poverty issues in the country. This study was conducted at Kuala Lumpur urban squatters concentrated destination in Kuala Lumpur, Malaysia. Mixed method approach was used where the quantitative outcome was compared with the qualitative data. In-depth interview which was used as the qualitative data collection method helped the researchers to justify the quantitative analysis which was done earlier. Descriptive statistics were utilized to obtain quantitative output. The results show that the community is not fully empowered and they are still dependent on outsiders’ help. It is hoped that the findings of this study will contribute to existing literature within urban poverty and socio-economic wellbeing spectrum.